Upaya Meningkatkan Hasil Belajar Siswa pada Pembelajaran PKN Kompetensi Dasar Memelihara Keutuhan NKRI Melalui Penggunaan Model STAD - Widarti Widarti (utile: Jurnal Kependidikan, 2018)
This research is carried out based on problems that include; (a) What is theimprovement of civic education learning achievement by applying the STAD model ofcooperative learning? (b) How does the cooperative learning method influence civiceducation learning motivation? This study uses action research as many as three rounds.Each round consists of four stages including; design, activity and observation, reflection, andrevision. The target of this study was the fifth grade students of Cipanas Elementary School inCitamiang District, Sukabumi City, 2015/2016 academic year. Data obtained in the form offormative test results, observation sheets of teaching and learning activities. From the resultsof the analysis it was found that students' learning achievements experienced an increasefrom cycle I to cycle III, namely cycle I (68.42%), cycle II (81.58%). The conclusion of thisstudy is that cooperative learning methods can have a positive effect on learning achievementand motivation of fifth grade students at Cipanas Elementary School in Citamiang District,Sukabumi City and this learning model can be used as an alternative to civic educationlearning.